Management features by municipal economy as difficult economic system - Оlenа Andrіeіeva (Cхід, 2013)
In the article the features of management and development of municipal economy are investigational as a difficult economic system. Certainly purpose, making elements, principles and management features by a municipal economy. Offered recommendations on the increase of management efficiency by a municipal economy on the basis of economic-financial, administrative-legal, organizational and informative measures. The necessity of creation of corresponding pre-conditions is well-proven with a help bringing existent administrative methods over and forms in accordance with the necessities of strategic and tactical development of local territories and necessities of his population on the basis of the effective and rational use of resources of territorial mass of city.